Penerapan Terapi Relaksasi untuk mengurangi kecemasan terhadap atlik paralimpik - Anggara, Onny Fransinata; acep ovel novari beny; Mufarrihul Hazin; Bakhrudin Al Habsy; Muhammad Reza (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
This research aims to investigate the impact of relaxation practices on the anxiety levels of Paralympic athletes from NPCI Sidoarjo. Ten athletes with varying levels of disabilities and competitive experiences were involved in this study. A qualitative approach was employed, collecting data through in-depth interviews and participatory observation. Findings indicated that relaxation practices, particularly through meditation and breathing techniques, had a positive impact on anxiety management. Statistical analysis results also demonstrated a significant decrease in anxiety scores after the relaxation practice period. These findings support stress and coping theory, emotion management, and highlight the importance of contextual factors in relaxation practices. Implications for coaching and the development of Paralympic athletes are discussed along with suggestions for future research.